The language of the New Testament : context, history, and development - Porter, Stanley E., 1956-; Pitts, Andrew W. (Linguistic biblical studies., 2013)
In The Language of the New Testament, Stanley E. Porter and Andrew W. Pitts assemble an international team of scholars whose work has focused on the Greek language of the earliest Christians in terms of its context, history and development.